2019
DOI: 10.1111/gbb.12583
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers to assess in utero effects of maternal opioid use: First steps toward understanding short‐ and long‐term neurodevelopmental sequelae

Abstract: Maternal opioid use disorder is common, resulting in significant neonatal morbidity and cost. Currently, it is not possible to predict which opioid‐exposed newborns will require pharmacotherapy for neonatal abstinence syndrome. Further, little is known regarding the effects of maternal opioid use disorder on the developing human brain. We hypothesized that novel methodologies utilizing fetal central nervous system‐derived extracellular vesicles isolated from maternal blood can address these gaps in knowledge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…Related to these complexities, a recent study isolated extracellular vesicles and synaptosomes from fetal neural samples in humans and observed complex changes in endogenous opioid and endocannabinoid receptor levels. 55,56 The study identified distinct effects between the two membrane preparations that were analyzed, and between the two opioids that participants in this study were using—buprenorphine and methadone. Moreover, microRNA sequencing revealed sex-dependent effects on expression pattern.…”
Section: Neurobehavioral Effects Of Developmental Opioid Exposures—humentioning
confidence: 98%
“…Related to these complexities, a recent study isolated extracellular vesicles and synaptosomes from fetal neural samples in humans and observed complex changes in endogenous opioid and endocannabinoid receptor levels. 55,56 The study identified distinct effects between the two membrane preparations that were analyzed, and between the two opioids that participants in this study were using—buprenorphine and methadone. Moreover, microRNA sequencing revealed sex-dependent effects on expression pattern.…”
Section: Neurobehavioral Effects Of Developmental Opioid Exposures—humentioning
confidence: 98%
“…OUD during pregnancy has been linked to low-birth weight, preterm birth, birth defects and NOWS. [2][3][4][5]18 Several factors associated with pregnancy outcomes have been shown to increase the risk of developing cardiovascular and metabolic diseases. [47][48][49] Low-birth weight and catch-up growth are established predictor of CVD risk, catch-up growth, a compensatory weight gain leading to rapid growth in infants or young children who are smaller for their age or adjusted age.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, a third concerning wave caused by synthetic opioids, specifically illicit fentanyl and fentanyl-like analogs, has been on an alarming rise since 2013. 1 Nevertheless, an understudied area related to the opioid epidemic is OUD during pregnancy, which results in a 5-fold increase in neonatal opioid withdrawal syndrome (NOWS) incidence, [2][3][4] affecting different body systems (eg, cardiovascular, gastrointestinal). NOWS severity is influenced by the length of exposure, type of opioid, and other licit and illicit substances that the mother uses.…”
mentioning
confidence: 99%
“…Medically supervised opioid withdrawal or detoxification in pregnant women with OUD is possible and has been suggested as an important strategy to decrease fetal exposure and opioidassociated fetal brain stress, [31][32][33][34][35][36][37][38] but needs to account for the possibility of maternal relapse and fetal withdrawals, which may result in fetal demise. 39 Rather, because it significantly reduces the risk of both relapse and withdrawal, MAT is the preferred treatment modality for pregnant women with OUD.…”
Section: Mats In the Pregnant Woman With Oudmentioning
confidence: 99%